2009
DOI: 10.1007/s10584-009-9713-0
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous knowledge related to climate variability and change: insights from droughts in semi-arid areas of former Makueni District, Kenya

Abstract: This article describes the indigenous knowledge (IK) that agro-pastoralists in larger Makueni District, Kenya hold and how they use it to monitor, mitigate and adapt to drought. It examines ways of integrating IK into formal monitoring, how to enhance its value and acceptability. Data was collected through target interviews, group discussions and questionnaires covering 127 households in eight villages. Daily rainfall data from 1961-2003 were analysed. Results show that agro-pastoralists hold IK on indicators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(83 citation statements)
references
References 23 publications
3
75
0
5
Order By: Relevance
“…The codesign, coproduction of knowledge, and coimplementation of practices imply the integration of multiple stakeholders' beliefs, perceptions, and interests, yet these are often conflicting (Stringer et al 2006, Lindenfeld et al 2014, MartĂ­n-LĂłpez and Montes 2015. For example, the integration of indigenous, local, and ecological knowledge into the scientific process has been recognized recently as a crucial feature of understanding diverse SESs, but is also one of the key challenges facing PBSESR (Ifejika Speranza et al 2010, Bohensky and Maru 2011, Tengö et al 2014. The integration of different groups and fostering of a unified or coherent voice might be impossible or even undesirable under particular contexts (Voß and Bornemann 2011).…”
Section: Accelerating Progress Toward Inter-and Transdisciplinary Intmentioning
confidence: 99%
“…The codesign, coproduction of knowledge, and coimplementation of practices imply the integration of multiple stakeholders' beliefs, perceptions, and interests, yet these are often conflicting (Stringer et al 2006, Lindenfeld et al 2014, MartĂ­n-LĂłpez and Montes 2015. For example, the integration of indigenous, local, and ecological knowledge into the scientific process has been recognized recently as a crucial feature of understanding diverse SESs, but is also one of the key challenges facing PBSESR (Ifejika Speranza et al 2010, Bohensky and Maru 2011, Tengö et al 2014. The integration of different groups and fostering of a unified or coherent voice might be impossible or even undesirable under particular contexts (Voß and Bornemann 2011).…”
Section: Accelerating Progress Toward Inter-and Transdisciplinary Intmentioning
confidence: 99%
“…Nonetheless, most of the eleven (11) items or statements are more sympathetic towards the efficacy of local knowledge. These items/statements were constructed based on our earlier interactions with local farmers and the literatures (see for instance, Ifejika Speranza et al, 2010;Orlove et al, 2010). They were rated on a 5-point Likert scale of 1-5.…”
Section: Farmers' Perceptions About the Nature Of Local And Scientifimentioning
confidence: 99%
“…Thus smallholder farmers value their ability to accurately observe and anticipate local conditions in various ways that serve their needs better than outside forecasts (see Onyango, 2009;Ouma, 2009). Elsewhere, it is acknowledged that local knowledge, at the least, plays a complementary role in generating climate information and understanding climate variability (see Ifejika Speranza et al, 2010;Orlove et al, 2010). The ability to anticipate changes at seasonal and shorter time scales and to adjust the farming practice accordingly, is a key element in creating resilience of indigenous farmers to the vagaries of weather conditions, thus serving as the basis for improving food security.…”
Section: Introductionmentioning
confidence: 99%
“…Ifejika Speranza et al (2009) stress the need to integrate Indigenous knowledge into education programmes in Kenya in order to maintain and strengthen culture. Ifejika Speranza et al (2009) also note the need to recognise that the preexisting stresses in many communities are a core reason in why otherwise resilient communities may have difficulties adapting to a climate changed world.…”
mentioning
confidence: 99%
“…Returning to the African continent, the third paper by Ifejika Speranza et al (2009) focuses on the Indigenous knowledge held by the agro-pastoralists in the Makueni District, Kenya. Interviews conducted by the authors in several villages identified how these agro-pastoralists incorporate Indigenous knowledge and meteorological forecasts into their planning decisions and how they use it to monitor, mitigate and adapt to drought.…”
mentioning
confidence: 99%